The Challenges and Prospect of Maritime Industry in Nigeria: Array - Nsan-Awaji, Ephraim Stephen (Danubius Working Papers, 2020)
Inland waterways are made up of navigable rivers, lakes, creeks, lagoons and canals. The movement of goods and services along inland waterways is one of the oldest means of transporting goods and services from one point to another. This was largely since inland water transportation offers the most economical, energy efficient and environmentally friendly means of transporting all types of cargoes from place to place. It also offered safe and cheaper transportation in areas with watercourses. Obviously, the economic development of most developing nations of Africa, including Nigeria, should reflect in the development, organization, coordination and management of this sea-borne trade, which is critical and cardinal to the development of international trade with other nations of the world. This is because, maritime-transport services duly serve as the propelling anchor and evolving force for the survival, hence, the formulation of execution of policies that disrupt the efficient running of this vital sub-economic system globally, will affect the efficiency and well-being of the enlarged society as well as the people. Nigeria is a major international trading nation in Africa, exporting large quantities of hydrocarbons to earn substantial revenue which accrue from crude oil export and are used mainly to fund huge trade in imports.